Uji Validitas dan Reliabelitas Instrumen Literasi Numerasi Materi Tata Surya untuk Siswa Tunanetra - Sarnita, Fitria; Adnyana, Putu Budi; Rapi, Ni Ketut (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
This study investigates the validity and reliability of a numeracy literacy instrument tailored for visually impaired students, focusing on solar system materials. The methodology involved distributing a questionnaire to three randomly selected experts who rated the instrument's content validity using the Content Validity Ratio (CVR) and the Content Validity Index (CVI). The results indicated that 9 out of 12 items were valid with CVI ? 0.68, while 3 items required revision. The reliability analysis, performed using Cronbach's Alpha, yielded a high value of 0.916, surpassing the critical threshold, thus confirming the instrument's consistency. These findings suggest that, with minor modifications, the instrument is both valid and reliable for assessing numeracy literacy among visually impaired students, highlighting its potential application in inclusive education settings.